Limit of (Cosine (X) - 1) over X

From ProofWiki
Jump to navigation Jump to search

Theorem

$\displaystyle \lim_{x \mathop \to 0} \frac {\map \cos x - 1} x = 0$


Proof 1

This proof works directly from the definition of the cosine function:


\(\displaystyle \cos x\) \(=\) \(\displaystyle \sum_{n \mathop = 0}^\infty \left({-1}\right)^n \frac {x^{2 n} }{\left({2 n}\right)!}\) Definition of Real Cosine Function
\(\displaystyle \) \(=\) \(\displaystyle \left({-1}\right)^0 \cdot \frac {x^{2 \cdot 0} } {\left({2 \cdot 0}\right)!} + \sum_{n \mathop = 1}^\infty \left({-1}\right)^n \frac {x^{2 n} } {\left({2 n}\right)!}\)
\(\displaystyle \) \(=\) \(\displaystyle 1 + \sum_{n \mathop = 1}^\infty \left({-1}\right)^n \frac {x^{2 n} } {\left({2 n}\right)!}\) Definition of Zero Factorial and Definition of Zeroth Power


\(\displaystyle \lim_{x \mathop \to 0} \ \frac{\cos \left({x}\right) - 1} x\) \(=\) \(\displaystyle \lim_{x \mathop \to 0} \ \frac{1 + \sum_{n \mathop = 1}^\infty \left({-1}\right)^n \frac {x^{2 n} } {\left({2 n}\right)!} - 1} x\)
\(\displaystyle \) \(=\) \(\displaystyle \lim_{x \mathop \to 0} \ \frac{\sum_{n \mathop = 1}^\infty \left({-1}\right)^n \frac {x^{2 n} } {\left({2 n}\right)!} } x\)
\(\displaystyle \) \(=\) \(\displaystyle \lim_{x \mathop \to 0} \ \frac{\sum_{n \mathop = 1}^\infty \left({-1}\right)^n \frac {x^{2 n - 1} } {\left({2 n - 1}\right)!} } 1\) Power Series is Differentiable on Interval of Convergence and L'Hôpital's Rule
\(\displaystyle \) \(=\) \(\displaystyle \lim_{x \mathop \to 0} \ \sum_{n \mathop = 1}^\infty \left({-1}\right)^n \frac {x^{2 n - 1} } {\left({2 n - 1}\right)!}\)


Now let:

$f_n \left({x}\right) = \left({-1}\right)^n \dfrac {x^{2n - 1} } {\left({2 n - 1}\right)!}$

Then for every $n \in \mathbb N_{\gt 0}$, and for all $x \in \left[{\frac 1 2 \,.\,.\, \frac 1 2}\right]$:

\(\displaystyle f_n \left({x}\right)\) \(\le\) \(\displaystyle \left \lvert \left({-1}\right)^n \frac {x^{2 n - 1} }{\left({2 n - 1}\right)!} \right \rvert\) \(\displaystyle \; = \frac { {\lvert x \rvert}^{2 n - 1} } {\left({2 n - 1}\right)!}\) Absolute Value Function is Completely Multiplicative
\(\displaystyle \) \(\le\) \(\displaystyle \frac 1 {2^{2 n - 1} \left({2 n - 1}\right)!}\) Power Function is Strictly Increasing over Positive Reals
\(\displaystyle \) \(\le\) \(\displaystyle \frac 1 {2^{2 n - 1} }\) because the factorial is strictly increasing
\(\displaystyle \) \(\le\) \(\displaystyle \frac 1 {2^n}\) because $n \ge 1 \iff 2n-1 \ge n$


But from the Geometric Series we have

$\displaystyle \sum_{n \mathop = 1}^\infty \frac 1 {2^n} = 2 < \infty$


By the Weierstrass M-Test, $\displaystyle \sum_{n \mathop = 1}^\infty f_n \left({x}\right)$ converges uniformly to some function $f$ on $\left[{\frac 1 2 \,.\,.\, \frac 1 2}\right]$.

But from Polynomial is Continuous, and the Uniform Limit Theorem $f$ is continuous on $\left[{\frac 1 2 \,.\,.\, \frac 1 2}\right]$.

So:

$\displaystyle \lim_{x \mathop \to 0} f \left({x}\right) = f \left({0}\right) = \sum_{n \mathop = 1}^\infty \left({-1}\right) \frac {0^{2 n - 1} } {\left({2 n - 1}\right)!} = 0$

$\blacksquare$


Proof 2

This proof assumes the truth of the Derivative of Cosine Function:


From Cosine of Zero is One:

$\cos 0 = 1$

From Derivative of Cosine Function:

$D_x \left({\cos x}\right) = - \sin x$

and by Derivative of Constant:

$D_x \left({-1}\right) = 0$

So by Sum Rule for Derivatives:

$D_x \left({\cos x - 1}\right) = - \sin x$

By Sine of Zero is Zero:

$\sin 0 = 0$

From Derivative of Identity Function:

$D_x \left({x}\right) = 1$


Thus L'Hôpital's Rule applies and so:

$\displaystyle \lim_{x \mathop \to 0} \frac {\cos x - 1} x = \lim_{x \mathop \to 0} \frac {-\sin x} 1 = \frac {-0} 1 = 0$

$\blacksquare$


Proof 3

\(\displaystyle \lim_{x \mathop \to 0} \ \frac {\cos x - 1} x\) \(=\) \(\displaystyle \lim_{x \mathop \to 0} \ \frac {\left({\cos x - 1}\right) \left({\cos x + 1}\right)} {x \left({\cos x + 1}\right)}\)
\(\displaystyle \) \(=\) \(\displaystyle \lim_{x \mathop \to 0} \ \frac {\cos^2 x - 1} {x \left({\cos x + 1}\right)}\)
\(\displaystyle \) \(=\) \(\displaystyle \lim_{x \mathop \to 0} \ \frac {-\sin^2 x} {x \left({\cos x + 1}\right)}\) Sum of Squares of Sine and Cosine
\(\displaystyle \) \(=\) \(\displaystyle \left({\lim_{x \mathop \to 0} \ \frac {\sin x} x}\right) \left({\lim_{x \mathop \to 0} \ \frac {-\sin x} {\cos x + 1} }\right)\) Product Rule for Limits of Functions
\(\displaystyle \) \(=\) \(\displaystyle 1 \times \left({\lim_{x \mathop \to 0} \ \frac{-\sin x} {\cos x + 1} }\right)\) Limit of Sine of X over X
\(\displaystyle \) \(=\) \(\displaystyle \frac {\lim_{x \mathop \to 0} \left({- \sin x}\right)} {\lim_{x \mathop \to 0} \left({\cos x + 1}\right)}\) Quotient Rule for Limits of Functions
\(\displaystyle \) \(=\) \(\displaystyle \frac 0 2\)
\(\displaystyle \) \(=\) \(\displaystyle 0\)

$\blacksquare$


Proof 4

\(\displaystyle \frac {\cos x - 1} x\) \(=\) \(\displaystyle \frac {\cos x - \cos 0} x\) Cosine of Zero is One
\(\displaystyle \) \(\to\) \(\displaystyle \left.{\dfrac {\mathrm d} {\mathrm dx} \cos x}\right \vert_{x \mathop = 0}\) as $x \to 0$, from definition of derivative at a point
\(\displaystyle \) \(=\) \(\displaystyle \sin x \vert_{x \mathop = 0}\) Derivative of Cosine Function
\(\displaystyle \) \(=\) \(\displaystyle 0\) Sine of Zero is Zero

$\blacksquare$